Lactic Acid Profile of Bali cattle during Rest Period Before Slaughtered - Siswanto Siswanto; I Nyoman Sulabda (Journal of Veterinary and Animal Sciences, 2020)
The animal products quality is influenced the physiological compounds in the blood, for example lactic acid. If blood lactic acid levels increase before slaughtering will be accelerate the rigor mortis of meat, thus faster handling is needed. Blood lactic acid also affects the appearance of flesh color of meat. The condition of animals before slaughter (rest period in quarantine) is very influential on rigor mortis. It is important to research blood lactic acid levels before animals are slaughtered. This research was conducted to determine the blood lactic acid levels of bali cattle during the rest period before the animal was slaughtered (ante mortem), so it can be predicted the quality of meat products. Purposive was chosen as a sampling method using elisa test as a determination of lactic acid levels. Fourtysamples of blood taken from cows to be slaughtered at Sanggaran Animal Abattoir, Denpasar, Bali. The results showed that the blood levels of lactic acid in cattle would be cut normally. This shows the quality of resting cattle before slaughter is good.